Prospectus Institiut Teknoloji MARA (MARA Institute Of Technology) School Of Applied Science: Course in Rubber Technology Plastics Technology - ITM, Institut Teknologi MARA (Utusan Melayu (Malaysia) Berhad, 1980)
During the last century and a half, two closely related classes of materials, rubber and plastics, have been introduced. These materials not only give rise to a challenge to the natural materials like wood, metal, cotton, leather, stone etc. but also make possible the manufacture of new products. Rubber and Plastics are used for the making of materials for road and air transport, in the clothing industry, domestic electricity, television, radio and the many domestic articles of everyday use. In the last thirty years the importance of plastics as a commercial material has grown enormously, not as cheap substitutes or as novelties but alongside other materials such as metals and wood. Rubber is a unique and remarkable material. With synthetic or manmade rubbers it is possible to a very large degree, to tailor properties to suit requirements. It has the elasticity required for many functions, besides abrasion and heat resistance, solvent resistance, chemical resistance and strength.